Development and Validation of the Revised Multicultural Ideology Scale in Germany and Luxembourg. Issue 1 (February 2023) - Stogianni, Maria; Berry, John W.; Grigoryev, Dmitry; Murdock, Elke; Schmidt, Lea-Marie; Back, Caroline
A revised version of the Multicultural Ideology Scale (rMCI) is currently being developed to measure endorsement of multiculturalism in different cultural contexts. This study, which is part of a wider cross-cultural research project, presents the first assessment of the rMCI scale in the German language. The measure aims to cover several attitudinal dimensions of multiculturalism, relevant to the integration of different ethnocultural groups: Cultural Maintenance, Equity/Inclusion, Social interaction, Essentialistic Boundaries, Extent of Differences, and Consequences of Diversity. Two independent datasets were acquired from Germany ( N  = 382) and Luxembourg ( N  = 148) to estimate the factor structure of the rMCI using different confirmatory factor analysis techniques. The findings suggest that a four-factor solution, including Cultural Maintenance, Equity/Inclusion, Social interaction, and Consequences of Diversity, was the best fit for the data. Most of these subscales demonstrated adequate psychometric properties (internal consistency, convergent, and discriminant validity). The four-factor model of the rMCI was partially invariant across the two ethnic groups and full measurement invariance was established across gender.